Community volunteers deliver integrated prevention and treatment services to reduce child wasting in Chad - Becquey, Elodie; Touré, Mariama; Djoufouna, Ahmed D.; Barba, Francisco; Affenou, Aldo; Diatta, Ampa Dogui; Dione, Malick; Sawadogo, Abdoulaye; Huybregts, Lieven (International Food Policy Research Institute, 2023)
Wasting is a persistent public health problem affecting 45 million children under five years of age worldwide. Wasting is responsible for the deaths of 875,000 children under the age of five every year. Children who survive often suffer from long-term cognitive and physical disabilities UNICEF, the World Health Organization, and the World Bank 2021; Black et al. 2013). Member countries of the World Health Assembly (WHA) have agreed to reduce and maintain the prevalence of wasting to less than 5 percent by 2025. Most Sahelian countries are off track to meet the WHA targets and in Chad, the prevalence of wasting is still unacceptably high at 14 percent and shows large regional disparities (UNICEF, the World Health Organization, and the World Bank 2020). While both wasting prevention and treatment programs hold the potential to reduce child wasting, substantial synergies can be expected when prevention is integrated with screening, referral, and treatment services. Such integration should happen at the community level to maximize the accessibility of services for caregivers and their children.